Przystępność tekstów w podręcznikach do nauczania języka polskiego jako obcego - Moździerz, Tomasz (Neofilolog, 2025)
The readability of texts is a crucial consideration in didactics. Educational materials provided to students should be challenging yet not incomprehensible. In glottodidactics, careful selection of content is paramount to stimulate learners’ development without discouraging them. This article explores the readability of Polish language textbooks across all proficiency levels. An analysis was conducted on 23 selected publications, from which 10 fragments containing 100–150 words each were extracted. The difficulty of these fragments was measured using the Gunning Fog Index and an algorithm available on the website jasnopis.pl. The results demonstrate a gradual increase in difficulty across both scales: from 4 on the Gunning Fog index and 2/7 on the Jasnopis scale at the A1 level to 7 on the Gunning Fog index and 4/7 on the Jasnopis scale at the C level. Although neither the Gunning Fog index nor the Jasnopis scale is specifically designed for glottodidactic purposes, the average readability values presented for each level may serve as a useful guide in selection and creation of supplementary materials beyond standard textbooks.